Combining ability of varieties and heterosis of divergent intervarietal crosses of yellow grain maize - Díaz Juárez, Roberto de la Cruz; Castillo-González, Fernando; Santacruz-Varela, Amalio; Gómez-Montiel, Noel Orlando; García-Zavala, J. Jesús; Muñoz-Orozco, Abel (Ecosistemas y Recursos Agropecuarios, 2023)
The estimation of genetic parameters provide makes it possible to decide the plant breeding methodologies to be applied in order to have better utilization of the germplasm. 32 yellow grain maize population from different origins were field evaluated, were subsequently selected eight with the better agronomic performance and wide genetic diversity, which were used to obtain 56 crosses (Griffing’s Method 1), these crosses were evaluated in two locations under a randomized complete block experimental design. The objective was to estimate the general (GCA) and specific combining ability (SCA), the predominant type of gene action, and to determine the presence of maternal (MatE) and reciprocal effects (RecE) for agronomics traits, as well as, to estimate heterosis for grain yield (GY) in yellow grain maize crosses. GY and six agronomic traits were quantified. Significant differences were found between genotypes, GCA and SCA for all traits. In addition, between environmental for plant height (PH), shelling coefficient, kernel length (KL), and GY. As well as for MatE and for Genotypes × Environmental, GCA × Environmental interactions for PH, KL, 100-kernels weight, female flowering days, prolificacy index and GY. Additive effects were predominant for traits evaluated. Otherwise, there is significance to MatE but not for RecE in the expression of the traits. Furthermore, there was positive heterosis in crosses yield. Combining ability and heterosis will serve to select the best varieties and include them in a breeding program for the Highlands Region of Mexico.
Keywords: Specific combining ability; General combining ability; Maternal effects; Yield heterosis; Zea mays L.